INTERAKSIONAL MODEL KOMUNIKASI PEMBANGUNAN DI ERA DEMASSIFIKASI - N. Wibawanti Ratna Amina (Bricolage : Jurnal Magister Ilmu Komunikasi, 2017)
Development model is always correlated with the Communication model evolves. Growth model to produce a top-down communication, Model Trickle down effect has resulted in a double take a step communication model. The Models turned out to create a gap of knowledge. The failure of the growth paradigm demands that the integral between growth and social intervention. These demands will have implications on the formation of interactive communication model development perspective. Although this perspective shortage theoretical foundation, this perspective provides the main instructions for implementing communication research. Keywords: Growth, Comuunicatian, gap, knowledge, interactive